Perbandingan Penggunaan Obat Rasional Berdasarkan Indikator WHO di Puskesmas Kecamatan antara Kota Depok dan Jakarta Selatan - Kardela, Widya; Andrajati, Retnosari; Supardi, Sudibyo (Jurnal Kefarmasian Indonesia, 2014)
Procurement and distribution of drugs to community health centers generally performed by health office districts, such as Depok City, but in the province of Jakarta conducted by the community health centers in sub district. The purpose of the study was to compare the rational drug use among community health centers in the district of Depok City and South Jakarta. This study used a cross-sectional design conducted in treatment and non- treatment community health centers in District X Depok City and district Y South Jakarta period MarchOctober 2011. Rational drug use data was collected in accordance with WHO procedure. Data was analyzed by Kruskal Walis test. Conclusion of the study shows that rational drug use based on prescribing indicators in community health centers in Depok City relatively better than South Jakarta, but no statistically significant (p> 0.05). Rational drug use based on patient care indicators in community health center South Jakarta is relatively better than Depok city, however, showed no statistically significant (p> 0.05). In contrast to the indicator of drug preparation time in health centers Depok relatively faster than South Jakarta, showed statistically significant (p